2013
DOI: 10.1038/bjc.2013.85
|View full text |Cite
|
Sign up to set email alerts
|

A randomised phase II/III trial of 3-weekly cisplatin-based sequential transarterial chemoembolisation vs embolisation alone for hepatocellular carcinoma

Abstract: Background:Transarterial chemoembolisation (TACE) has not been shown to be superior to bland embolisation (TAE) for treatment of hepatocellular carcinoma (HCC).Methods:We conducted a randomised phase II/III trial in patients with untreated HCC. Patients were randomised to TAE with polyvinyl alcohol (PVA) particles alone or sequential TACE (sTACE) in which cisplatin 50 mg was administered intrarterially 4–6 h before PVA embolisation. Treatment was repeated 3-weekly for up to three treatments. The primary endpoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
102
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(126 citation statements)
references
References 34 publications
6
102
1
1
Order By: Relevance
“…Although many clinical trials of TACE alone or targeted agents in combination with TACE use OS as a primary endpoint, it takes a long time before its effects are proved [11][12][13] . Furthermore, the OS benefit is diluted by prolonged post-progression survival [14] , because post-trial treatments such as intra-arterial infusion chemotherapy, sorafenib, or other trial agents (including regorafenib, lenvatinib, or immunotherapy) can have a chance of marked antitumor effect, resulting in longer post-progression survival irrespective both in the testing and control arms.…”
Section: Introductionmentioning
confidence: 99%
“…Although many clinical trials of TACE alone or targeted agents in combination with TACE use OS as a primary endpoint, it takes a long time before its effects are proved [11][12][13] . Furthermore, the OS benefit is diluted by prolonged post-progression survival [14] , because post-trial treatments such as intra-arterial infusion chemotherapy, sorafenib, or other trial agents (including regorafenib, lenvatinib, or immunotherapy) can have a chance of marked antitumor effect, resulting in longer post-progression survival irrespective both in the testing and control arms.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in a meta-analysis of seven randomized clinical trials of patients with unresectable HCC by Llovet et al [10] embolization was shown to provide a significant survival benefit when compared to observation alone. Although TACE is regarded by some as the superior method of embolization, recently published randomized clinical trial data have demonstrated no significant survival difference between TACE, DEB TACE and bland HAE [1113]. Consequently, the most recently published National Comprehensive Cancer Network consensus guidelines for the treatment of HCC suggest embolization, either bland HAE or TACE, as the standard of care for patients with intermediate/advanced HCC without extra hepatic spread or main portal vein involvement [14]…”
Section: Introductionmentioning
confidence: 99%
“…Optimal therapy is limited by a paucity of proven adjuvant therapies to potentiate embolotherapy-induced ischemia. Prospective randomized trials have demonstrated TACE and TAE to be equally effective with respect to survival, and none of the currently used chemotherapeutic agents has demonstrated superiority to others (713). …”
mentioning
confidence: 99%